2017
DOI: 10.21037/atm.2017.06.06
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an evaluation mode with multiple primary outcomes based on combination of diseases and symptoms in TCM clinical trials

Abstract: The development of a scientific evaluation tool is a prerequisite to reflect the efficacy of traditional Chinese medicine (TCM). At present, separate analysis of each outcome is the most commonly used method in randomized controlled trials (RCTs) of TCM, while this method has been reported to have some limitations. Combination evaluation of multiple primary outcomes including diseases and symptoms can reflect the efficacy of TCM comprehensively and objectively. Now, several multivariate statistical methods hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Since the holism perspective of TCM, as well as the multidimensional of the reported outcomes (patient-reported, laboratory test, clinician-rated and TCM syndrome outcomes, etc. ), it is not practical to identify a single most important outcome as the primary outcome to summarize the effect of CHM [ 35 ]. Our previous study also had proposed an efficacy evaluation system with multiple primary outcomes, which is based on the holism benefit of TCM, integrated the primary outcome by three domains: western medicine-specific outcome, TCM syndrome outcome, and quality of life [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the holism perspective of TCM, as well as the multidimensional of the reported outcomes (patient-reported, laboratory test, clinician-rated and TCM syndrome outcomes, etc. ), it is not practical to identify a single most important outcome as the primary outcome to summarize the effect of CHM [ 35 ]. Our previous study also had proposed an efficacy evaluation system with multiple primary outcomes, which is based on the holism benefit of TCM, integrated the primary outcome by three domains: western medicine-specific outcome, TCM syndrome outcome, and quality of life [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reporting more than one primary outcome in CHM trials may be appropriate because a single measure may not sufficiently characterize the effect of a Chinese herbal formula on a broad set of domains [ 10 , 11 ]. Multidimensional primary outcomes, which can incorporate the laboratory test, traditional Chinese medicine- (TCM-) diagnosed information (e.g., tongue coat, pulse, face color, and mind), and clinician-concerned and patient-reported outcomes have been proposed [ 12 , 13 ]. When there is a lack of clear consensus on the most important clinical outcome, combined with the need to examine clinical effectiveness on related outcomes spanning disparate domains, encourage the use of multiple primary outcomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since we aim to capture a holistic effect of YBI across the multiple domains of HAP, we propose to use the global statistical test (GST) to assess the efficacy of the intervention. 35 36 However, in view of non-availability of preliminary data, unknown nature of correlations among the outcome variables and their distribution, we prefer to choose a sample size of n1−n2=100, which is in line with the adequate sample size proposed for 10 multiple outcomes (K), under the simulations reported for sample size calculations with computation of the global treatment effect under various possible settings by Huang et al 35 Further, since the reported efficiency of GST to summarise a treatment's merit is not compromised with small sample sizes, we could avoid the risk of being underpowered. 37 Further, keeping in view of the attrition rate of 25% over 6 months, we derived a sample size of n=250 for the present study.…”
Section: Sample Sizementioning
confidence: 99%
“…Therefore, how to predict the drug combination of these TCM and WM and assess the efficacy and side effects is valuable for novel drug design. At present, RCTs have been generally used to assess the clinical efficacy of TCM (Hu et al, 2017). For example, a meta-analysis of RCTs has shown that TCM significantly improved analog scale, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and total effectiveness rates of knee osteoarthritis.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Therefore, the optimization of the ADME properties of lead compounds may be a critical factor that determines whether the drug can be successfully developed (MacCoss and Baillie, 2004). Many clinical studies including randomized controlled trials (RCTs) of the herbs have been conducted, some demonstrating hepatotoxicity and toxicity (Hu et al, 2017). However, because the extraction and isolation of compounds derived from herbs are costly and time-consuming, as well as only a few of them have satisfactory ADME properties and less side effects, there is an urgent need to develop a fast and effective novel strategy for identifying potential active compounds.…”
Section: Introductionmentioning
confidence: 99%